A study on consumption of iodine by an individual in selected area in Tangail, Bangladesh (Asian Journal of Medical and Biological Research, 2016)
The purpose of this study was to assess consumption of iodized salt by an individual (g/person/day) in a village of Tangail district and to compute the intake of iodine by an individual (?g/person/day) in a village in Tangail district. Vacuum evaporated salt was used for the study. The salt was analyzed for chemical composition and iodine content. Various physico-chemical characteristics of salt were analyzed to determine the moisture content, chloride content (as NaCl), water insoluble matter, pH, calcium content, magnesium content, and iodine content. Study was done among 68 families for a period of 35 days. Family member was divided into 4 groups according to their age - below 5 years, 5-9 years, 10-19 years and above 19 years. Male member among the family members was minimum 1 and maximum was 8. In case of female, minimum number was 1 and maximum number was 7. Among family members, 45.58% were male and 54.42% were female consumers. Percentage of salt consumers among Family members below 5 years was 11.81%, in 5-9 years it was 6.94%. Percentage of salt consumer in family members between 10-19 years was 24.54%, and salt consumers percentage in family members above 19 years was 56.71%. By statistical analysis among data, mean value of salt consumption g/ person /day was 12.49, standard deviation was 2.05 and minimum salt consumption among family members was 10.02 g/person/day and maximum value was 18.47 g/person/day. Among the family members, mean value of intake of iodine was 399.68 ?g/person/day, maximum intake of iodine was 591.04 ?g/person/day and minimum intake was 320.64 ?g/person/day. Finding of this study was that, salt consumption rate are satisfactory and intake of iodine by individual in village Chamuria in Tangail district is adequate to avoid Iodine Deficiency Disorder in normal health condition.Asian J. Med. Biol. Res. June 2016, 2(2): 341-347